Studying physics - Sands, David 1960- (Palgrave study guides, 2004)
An essential guide to the undergraduate wishing to develop skills in physics. Drawing on physics education research and the author's own extensive experience in teaching, this book addresses the skills needed by the undergraduate to become a physicist